The Effects of Social Media Influencers’ Source Credibility on their Ascribed Opinion Leadership and Consumers’ Purchase Intention - Tille, Melanie (2020)
In the last years, social media with its networking platforms and online communities gained extreme popularity. With this emergence, brands all around the globe became well aware of people’s increasing daily social media activities on platforms such as Instagram. Consequently, influencer marketing got extremely important for businesses as a new marketing communication tool. However, there are concerns around the social media influencers’ perceived source credibility and their impact on consumers’ purchase intentions. The present research focuses on the Portuguese and German market and investigates how the perceived source credibility of Instagram social media influencers and its dimensions, namely attractiveness, trustworthiness, and expertise affect their ascribed opinion leadership and consequently influence consumers’ purchase intentions. As well as it examines the role of consumers’ self-esteem on the relationship between ascribed opinion leadership and consumers’ purchase intention. An online survey was conducted to collect data from 467 respondents from Portugal and Germany. The statistical analysis of the questionnaire was performed with structural equation modeling (SEM). The results of the study indicate that especially the influencers’ attractiveness as one of the source credibility dimensions has a positive impact on their ascribed opinion leadership. The findings provide evidence that social media influencers perceived as opinion leaders positively influence consumers’ purchase intention. Based on these results, further research directions and practical implications are provided.